Investigations on the properties of an acrylamide-modified melamine resin. Part II. Prediction of polymer properties - Dębska, B.; Wianowska, E. (Polimery, 2022)
Classification and graphical presentation of experimental data aets were used in the SCANKEE system to predict properties of an acrylamide-modified melamine resin. The SCANKEE system is based on a specific formalism of process representation known as the knowledge association (Scheme 1).